2023
DOI: 10.3390/cancers15164037
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Population-Based Studies of Chronic Bowel Symptoms in Cancer Survivors following Pelvic Radiotherapy

Abstract: Pelvic radiotherapy can damage surrounding tissue and organs, causing chronic conditions including bowel symptoms. We systematically identified quantitative, population-based studies of patient-reported bowel symptoms following pelvic radiotherapy to synthesize evidence of symptom type, prevalence, and severity. Medline, CINAHL, EMBASE, and PsychINFO were searched from inception to September 2022. Following independent screening of titles, abstracts, and full-texts, population and study characteristics and sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 70 publications
(624 reference statements)
0
1
0
Order By: Relevance
“…Questionnaire-based studies have reported varied prevalence of these symptoms and, perhaps more importantly, an associated decrease in overall quality of life (QoL) and across various QoL domains (e.g. [4][5][6]). However, few studies have used qualitative methods to explore survivors' experiences of living with these bowel symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Questionnaire-based studies have reported varied prevalence of these symptoms and, perhaps more importantly, an associated decrease in overall quality of life (QoL) and across various QoL domains (e.g. [4][5][6]). However, few studies have used qualitative methods to explore survivors' experiences of living with these bowel symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…The bowel symptoms that people treated with pelvic radiation may experience are wide-ranging and include urgency, frequency, bleeding, incontinence, mucous discharge, diarrhoea, excess wind, constipation and pain. Questionnaire-based studies have reported varied prevalence of these symptoms and, perhaps more importantly, an associated decrease in overall quality-of-life (QoL) and across various QoL domains (e.g., [4][5][6]). However, few studies have used qualitative methods to explore survivors' experiences of living with these bowel symptoms.…”
Section: Introductionmentioning
confidence: 99%